Abundance of primates in Ayer Hitam Forest, Puchong, Selangor - Zakaria, Mohamed; Topani, Rahmat (Universiti Putra Malaysia Press, 1999)
A study on the abundance and distribution of primates was conducted in Ayer Hitam Forest Reserve, Puchong, Selangor (AHFR). The main objective of this study was to examine the species composition and density of primates in the area. A total of nine transect lines were established and each line was walked four times during the study period. The total length of transect walked was 34,080 meters. The density was calculated using DISTANCE program V 2.2. The result showed that only five species of primates from a total of ten species present in Peninsular Malaysia were recorded. The species recorded were Presbytis melalophos (Banded-leaf Monkey), P. obscura (Duskyleaf Monkey), Hylobates lar (White-handed Gibbon), Macaca nemestrina (Pig-tailed Macaque) and M. fascicularis (Long-tailed Macaque) with the densities of 0.21, 0.09, 0.08, 0.07 and 0.04 individuals per hectare, respectively. The largest group size was demonstrated by P. melalophos (4.0 individuals/group) followed by M. fascicularis (2.6 individuals/group), P. obscura (2.5 individuals/group), H. lar (2.3 individuals/group) and M. nemestrina (1.6 individuals/group). The group density of all primates was 0.19 groups/ha. The density and group size of primates in AHFR are relatively lower compared to other areas in Peninsular Malaysia. Illegal hunting and over hunting activities by the Orang Asli and the shrinking forest size may contribute to the low density of primates in AHFR.